2015
DOI: 10.1123/jsep.2015-0069
|View full text |Cite
|
Sign up to set email alerts
|

Cognitively Engaging Chronic Physical Activity, But Not Aerobic Exercise, Affects Executive Functions in Primary School Children: A Group-Randomized Controlled Trial

Abstract: Although the positive effects of different kinds of physical activity (PA) on cognitive functioning have already been demonstrated in a variety of studies, the role of cognitive engagement in promoting children’s executive functions is still unclear. The aim of the current study was therefore to investigate the effects of two qualitatively different chronic PA interventions on executive functions in primary school children. Children (N = 181) aged between 10 and 12 years were assigned to either a 6-week physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
282
7
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 237 publications
(315 citation statements)
references
References 72 publications
11
282
7
15
Order By: Relevance
“…Tasks requiring less executive control were unaffected by the FITKids intervention. Schmidt et al 54 found that in 10- to 12-year-old children the group that participated in a cognitively- and physically-demanding exercise intervention (team games) showed more improvement from pre-test to post-test on cognitive flexibility (ie, being able to shift from one task to another) than the group receiving an aerobic intervention with low cognitive demands or the group receiving standard PE with low physical and low cognitive demands. Performance on the other two executive function subcomponents (ie, updating and inhibition) were similar between groups.…”
Section: Resultsmentioning
confidence: 99%
“…Tasks requiring less executive control were unaffected by the FITKids intervention. Schmidt et al 54 found that in 10- to 12-year-old children the group that participated in a cognitively- and physically-demanding exercise intervention (team games) showed more improvement from pre-test to post-test on cognitive flexibility (ie, being able to shift from one task to another) than the group receiving an aerobic intervention with low cognitive demands or the group receiving standard PE with low physical and low cognitive demands. Performance on the other two executive function subcomponents (ie, updating and inhibition) were similar between groups.…”
Section: Resultsmentioning
confidence: 99%
“…Adolescents might benefit as cognitive flexibility seems to be prone to positive changes of PA throughout later stages of child development. Therefore, one might speculate that aspects of executive functions which are not yet fully developed (cognitive flexibility) might be easier to change [27]. The relationship between age and the responsiveness to acute PA in terms of benefits on executive functions needs to be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only few studies examining cognitive engagement comprised in PA have tried to measure the cognitive challenges of specific PA. Mainly observational data [27,28] or a more general measure of engagement in the activity [8] has been used. However, a subjective rating on the individual level seems to be important in order to consider cognitive overload as a confounding variable.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study [51] was able to demonstrate that a 6-week, cognitively demanding sports game intervention, but not a pure aerobic exercise intervention, had a positive influence on the cognitive flexibility of primary school children. In order to have the largest possible effect, Moreau and Conway [52] recommend a combined physical and cognitive training programme.…”
Section: Introductionmentioning
confidence: 99%